Changes in the bidirectional sodium flux across the intestinal mucosa in Crohn's disease. Issue 3 (March 1975) - Allan, R; Steinberg, D M; Dixon, K; Cooke, W T
Abstract : Bidirectional sodium flux across the intestinal mucosa was measured in a group of 10 patients with Crohn's disease treated in the past by panproctocolectomy with ileostomy and compared with a similarly treated group of 11 patients with ulcerative colitis. All of them were in good health at the time of the study and a recent radiological examination of the small intestine was normal. A significant reduction in bidirectional sodium flux was found in those patients with Crohn's disease and suggests that the intestinal mucosa is involved to a greater extent than can be judged by radiological appearances alone. This adds weight to the concept that Crohn's diseases is a diffuse rather than a focal lesion of the gastrointestinal tract.